Urine Trouble! Different Shades of Yellow and How Urinalysis Can Help Our Patients - Cox, Sherri (Wildlife Rehabilitation Bulletin, 2017)
Analyzing urine is an important and inexpensive laboratory test that can be done in a wildlife rehabilitation facility. From basic in–house tests to more in depth analysis assisted by a veterinarian or veterinary technician, urinalysis can tell a lot about what might be happening (or not happening!) with wildlife, including various urinary tract diseases and as an indicator of dehydration. This paper focuses on mammal urinalysis and covers basic physiology, simple diagnostic tests and their interpretation, and possible treatments that may be indicated.